Sexual hegemony - Chitty, Christopher, 1983-2015 (Theory Q., 2020)
"Christopher Chitty was a graduate student and activist at UC-Santa Cruz who committed suicide in 2015. The project that Chitty left behind, entitled SEXUAL HEGEMONY, reveals how the policing of male homosexuality happened in conjunction with the establishment of capitalist economies across Europe and the U.S. Writing against a thesis of modernization in which sexual freedom advances alongside the development of commodity production and state formation, Chitty instead shows how the rise of capitalism has embedded a bourgeois sexual hegemony into property relations, economic crises, and political institutions. Drawing on queer theory, Marxism, Foucault, Gramsci, and world-systems-analysis, Chitty demonstrates that male same-sex intimacy and sex have systematically been constructed as problematic for bourgeois polities. The book begins with an introduction by Christopher Nealon that situates Chitty's work among new scholarship bringing Marxism into conversation with queer theory, and that speculates on some of the Marxist feminist texts that might have helped extend Chitty's limited analysis of lesbian and other non-male queer sexualities. Chitty's own work begins by considering Michel Foucault's idea that sexuality arises from the discourse of sexual science. Instead, Chitty argues that sexuality came into being as a result of the contradiction between the forces and relations of production inherent in the development of capitalism. The book's chapters proceed in chronological order, tracking the politicization of male homosexuality in Florence, Amsterdam, London, Paris, and New York. Chitty considers the secular offices of the late medieval and early modern Mediterranean world, which employed a sliding scale of penalties to regulate a flourishing culture of sodomy in Florence. Then he considers Atlantic seafaring culture of London and Amsterdam of the seventeenth and eighteenth centuries, and public urinal design in Paris of the nineteenth and twentieth centuries. Although unfinished, SEXUAL HEGEMONY is theoretically bold. It will make an important contribution to Marxist queer theory, early modern studies, and studies of sexuality"--